System of activities to develop communication skills through Plastic Education in Preschool grade children - Yanes Tenreyro, Yilian (2022)
The adequate development of communication skills in the students of the “José Luis Tassende” Special School that cares for children with language disorders, which encourages an efficient insertion into general education, still presents some difficulties, especially after this long stage of lockdown. The following work has the objective of designing a system of activities that takes advantage of all the benefits that Plastic Education provides for this purpose and favors the development of communication skills in Preschool grade children. This research is applied in a sample of 12 children between 4 and 5 years old. After a study it was found that despite this topic being of interest to many specialists, there are still shortcomings in terms of strategies for working specifically with these children on the topic. In the development of the investigation the methods of the theoretical level were used: analytical-synthetic, historical-logical, inductive-deductive, modeling and systemic-integral; from the empirical level: observation, interview, document analysis, discussion group and the criteria of specialists. The proposal has been conceived looking for new spaces and ways of expression for them, allowing a greater integration with the community that enriches their experiences, promoting the insertion of the family and making use of technology as an educational tool that allows it to be applied also in a blended way. . Their contribution is given in the implemented activity system that shows great acceptance and improvements in the expression capacity of these children..